Distinct role of lymphocyte function-associated antigen-1 in mediating effective cytolytic activity by cytotoxic T lymphocytes. - Anikeeva, N; Somersalo, K; Sims, T; Thomas, V; Dustin, M; Sykulev, Y (2005)
Lymphocyte function-associated antigen-1 (LFA-1) interaction with intercellular adhesion molecules (ICAMs) facilitates T cell antigen receptor (TCR)-mediated killing. To dissect TCR and LFA-1 contributions, we evaluated cytolytic activity and granule release by cytotoxic T lymphocytes (CTL) as well as intracellular granule redistribution and morphology of CTL stimulated with natural TCR ligand in the presence or absence of LFA-1 engagement. Although other adhesion mechanisms, e.g., CD2-CD58 interaction, could substitute for LFA-1 to trigger CTL degranulation, productive LFA-1 ligation was indispensable for effective target cell lysis by the released granules. LFA-1-mediated adhesion to glass-supported bilayers containing intercellular adhesion molecule-1 was characterized by a much larger junction area, marked by LFA-1 segregation, and a more compact cell shape compared with those observed for CD2-mediated adhesion to bilayers containing CD58. A larger contact induced by intercellular adhesion molecule 1 determined a unique positioning of granules near the interface. These data provide evidence that LFA-1 delivers a distinct signal essential for directing released cytolytic granules to the surface of antigen-bearing target cells to mediate the effective destruction of these cells by CTL.